Accessibility of reproductive health services among women living in the informal settlements of Mathare slums, Nairobi City County, Kenya - Rotich, Janet C.; Osero, Justus O.; Gitonga, Elphas (International Journal Of Community Medicine And Public Health, 2024)
Background: This study sought to determine the health facility-related factors and social factors associated with the accessibility of reproductive health services (RHS) among women living in the informal settlements of Mathare slums, Nairobi City County, Kenya. Methods: This cross-sectional study focused on Nairobi County, Kenya, specifically targeting Mathare slums, known for poor reproductive health (PRH) indicators among women. Three hundred women were randomly recruited from four villages (Mathare 3B, Mathare 4A, Kosovo, and Mathare village 2). Results: The majority of respondents were aged 18-29 years (48.7%), had primary education (61.7%), were married (58.7%), and unemployed (69.3%). Significant associations were observed between accessibility and the woman's age (χ2=83.013, df=1, p<0.001), education level (p<0.001), marital status (p<0.001), and employment status (χp<0.001). Significant health facility barriers to accessibility encompassed long distances to health facilities (p<0.001), transportation cost constraints (p<0.001), difficult terrain (p<0.001), cost of services (p<0.001), services provided by health facilities (p<0.001), and availability of required medications (p<0.001). Discouragement by friends or family (p<0.001), the perceived influence of age on RHS accessibility (p<0.001), the perceived influence of education level on RHS choices (p=0.014), and the perceived role of a spouse in influencing RHS (p=0.002) were all significant social factors associated with accessibility to RHS. Conclusions: Health facilities and social factors presented complex challenges, including geographical barriers, transportation costs, and medication availability, while spouse involvement, education's influence, and familial discussions positively impacted accessibility.